Eksplorasi Penerapan Pendekatan Scientific Ditinjau dari Pengetahuan Pedagogik Guru - Muhammad Ali P; Suryadi Ishak (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2019)
The main instrument in this study is the researcher himself and his supporting instruments are the teacher's pedagogical knowledge test, learning observation sheet, and interview. The subjects of the study were mathematics teachers at SMP Negeri 1 Polewali, SMP Negeri 2 Polewali, and SMP Negeri 3 Polewali, which were then chosen by two people from each school. The results obtained from this study are the first based on the results of pedagogical tests given to research subjects, namely there are 2 subjects that fall into the category of high pedagogical knowledge and there are 4 subjects that fall into the category of low pedagogic knowledge and based on interviews the results show subjects that fall into the knowledge category High pedagogic generally understands how the application of scientific approaches in mathematics learning because they have frequently participated in training related to the scientific approach, whereas subjects with low pedagogic knowledge category only one subject understands the application of the scientific approach because they are active in the training carried out by the relevant offices.and for the other 3 subjects they did not really understand the scientific approach because they had only participated in the training once. Based on observations, it shows that (1) subjects who have a high pedagogical knowledge category are generally good in applying learning steps because it is clear in directing students in the learning process so that some students are able to follow them well. (2) subjects who have a low pedagogical knowledge category are generally not good at implementing learning steps because they are not clear in directing students in the learning process so that students cannot follow them well.